12t-8m=-52

Simple and best practice solution for 12t-8m=-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12t-8m=-52 equation:


Simplifying
12t + -8m = -52

Reorder the terms:
-8m + 12t = -52

Solving
-8m + 12t = -52

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-12t' to each side of the equation.
-8m + 12t + -12t = -52 + -12t

Combine like terms: 12t + -12t = 0
-8m + 0 = -52 + -12t
-8m = -52 + -12t

Divide each side by '-8'.
m = 6.5 + 1.5t

Simplifying
m = 6.5 + 1.5t

See similar equations:

| 4.2+4=3x+9.4 | | (3x-9)/(x-4) | | -250x-3= | | b-7/4= | | B-7/4 | | 9(x+8)+12=8(x+8)10 | | x6/x3= | | 3.5=-7y+21 | | 9(x+8)*12=8(x+8)+10 | | (10+10)x+x=2 | | 21+3x+1=57 | | 14(8+12)= | | f(x)=-x^2-4x-8 | | -m+12=-9 | | (4a+3)-8=4+2a | | log*5*(x-4)=-1 | | 3/7=4/8 | | 1.5(10w+20)=3+2w | | 3x^2+4=18 | | 2y=y+37 | | 8y+9y+4=18 | | 3.14=3.14r^2/4 | | 7-log*9*(x+6)=6 | | 5x+7-3x=3x+12 | | 3(9.99)+5(1.29)= | | r(x)=2x-0.03x^2 | | 4y-2x-12=0 | | 4(p+5)=48 | | 78/x | | 0x+10y=-10 | | 48x^2=27x | | x+x+1+10=1 |

Equations solver categories